The effectiveness of social media based on photo and video sharing to-wards online purchase intention - Daru Asih; Teofilus Teofilus; Timotius FCW Sutrisno; Cynthia Yoana (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2020)
Internet users in Indonesia have reached 88.1 million and around 79 million are active social media users. The high phenomenon of using social media which is considered quite effective for promotion and sales is used by marketers in developing their business through online marketing on social media, one of which is Instagram. Instagram becomes one of the favorite social media that can help companies simplify their business products and services. Through Instagram, entrepreneurs can interact with consumers by sharing photos and videos. For some people, online purchases made through Instagram are considered more effective and efficient in creating online purchase intentions. The purpose of this research is to find out whether Instagram's social media marketing can influence interest in buying online through mediating variables of brand awareness, value awareness, and price awareness. The research method used is quantitative research with partial least square analysis. This study used a questionnaire and was measured with a Likert scale on 240 respondents of SME's customers. The results of this study indicate that Instagram social media marketing can make online purchase intentions without additional assistance by mediating variables brand awareness, value awareness, and price awareness.